Exploring the Relationship between Moral Decision-Making and Emotional Intelligence - Nyamori, Divine (International Journal of Philosophy, 2024)
Purpose: The general objective of the study was to explore the relationship between moral decision- making and emotional intelligence. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the relationship between moral decision- making and emotional intelligence. Preliminary empirical review revealed that emotional intelligence significantly influences individuals' ability to make ethically sound decisions, as evidenced by positive correlations between emotional intelligence and various aspects of moral decision-making. It found that individuals with higher emotional intelligence demonstrated superior emotional awareness, regulation, and empathy, enabling them to navigate moral dilemmas more effectively. The study highlighted the practical implications of these findings, suggesting that interventions aimed at enhancing emotional intelligence could promote ethical behavior in educational, organizational, and societal contexts. Overall, the research provided valuable insights into the intricate interplay between emotional intelligence and morality, informing strategies for fostering ethical leadership and social responsibility. Unique Contribution to Theory, Practice and Policy: The Social Learning theory, Cognitive Developmental theory and Dual Process theory may be used to anchor future studies on moral decision- making and emotional intelligence. The study offered recommendations that contributed significantly to theory, practice, and policy. It suggested further investigation into the underlying mechanisms of the relationship between moral decision-making and emotional intelligence. Practical implications included integrating emotional intelligence training into educational curricula and organizational practices, fostering ethical leadership and decision-making. Policy-wise, the study advocated for the integration of emotional intelligence and ethical education initiatives into broader societal frameworks. Collaboration among stakeholders was recommended to design evidence-based interventions promoting moral development and emotional competence, ultimately contributing to positive social change. Keywords: Moral Decision-Making, Emotional Intelligence, Education, Leadership, Ethical Dilemmas, Interventions, Stakeholders, Collaboration